Получение и свойства пористого карбида кремния - Svetlichnaya, L. A.; Moskovchenko, N. N.; Serba, P. V. (PE "Politekhperiodika", Book and Journal Publishers, 2005)
The methods of obtaining porous silicon carbide, its properties, and the influence of electrolyte composition, etching time, and current density on the morphology of the porous layer are discussed, as well as the dependence of pore structure on substrate doping. The results are compared with data on porous silicon.